“금오3호”의 벼 잎도열병 저항성 특성 및 저항성 연관 마커 탐색 - 이종희(Jong-Hee Lee); 곽도연(Do-Yeon Kwak); 박동수(Dong-Soo Park); 노재환(Jae-Hwan Roh); 강종래(Jong-Rae Kang); 김춘송(Choon-Song Kim); 전명기(Myeong-Gi Jeon); 여운상(Un-Sang Yeo); 이기환(Gihwan Yi); 신문식(Mun-Sik Shin); 오병근(Byeong-Geun Oh); 황흥구(Hung-Goo Hwang) (Korean journal of breeding, 2008)
Rice blast resistance is considered one of the most important traits in rice breeding and the disease, caused by Magnaporthe grisea Barr, has brought significant crop losses annually. Moreover, breakdown of resistance normally occurs in two to five years after cultivar release, thus a more durable resistance is needed for better control of this disease. We developed a new variety, Keumo3, which showed strong resistance to leaf blast. It was tested in 2003 to 2007 at fourteen blast nursery sites covering entire rice-growing regions of South Korea. It showed resistance reactions in 12 regions and moderate in 2 regions without showing susceptible reactions. Durability test by sequential planting method indicated that this variety had better resistance. Results showed that Keumo3 was incompatible against 19 blast isolates with the exception of KI101 by artificial inoculation. To understand the genetic control of blast resistance in rice cultivar Keumo3 and facilitate its utilization, recombinant inbred lines (RIL) consisting of 290 F5 lines derived from Akidagomachi/Keumo3 were analyzed and genotyped with Pizt InDel marker zt56591. The recombination value between the marker allele of zt56591 and bioassay data of blast nursery test was 1.1%. These results indicated that MAS can be applied in selecting breeding populations for blast resistance using zt56591 as DNA marker.